The Influence of Service Quality and Promotion on Consumer Loyalty Through Customer Satisfaction as an Intervening Variable - Haryanti, Denny Septa; Hermawanti, Nanik; Prilyana, Cindy; Anggiani, Sarfilianty (Master of Management, Faculty of Economics and Business, Diponegoro University, 2024)
This research aims to examine and analyze the influence of Service Quality and Promotion on Consumer Loyalty through Customer Satisfaction as an intervening variable for customers at Sulawesi Grilled Fish. The dependent variable used in this research is Consumer Loyalty (Y), the intervening variable used is Customer Satisfaction (Z), while the independent variables used are Service Quality (X1) and Promotion (X2). The sample in this study was 96 respondents. The sampling technique uses purposive sampling with the criteria being that the respondent is at least 18 years old and has made at least 2 purchases. The analytical method used is Convergent Validity, Discriminant Validity. Composite Reliability, Inner model. The results of the research conducted show that Service Quality and Promotion have a positive and significant effect on Customer Satisfaction, the Service Quality and Promotion variables have a positive and significant effect on Consumer Loyalty, the Service Quality variable has a positive and significant effect on Consumer Loyalty through Customer Satisfaction, and the Promotion variable has an effect positive and significant towards Customer Loyalty through Customer Satisfaction.